Reproductive Effort of Some Annual and Perennial Plant Species: Impact of Successional Sequence, Habitat Conditions and Plant Size: Impact of Successional Sequence on Plants - Shaukat, Syed Shahid; Khan, Moazzam Ali; Zaidi, Sahar; Siddiqui, Muhammad Faheem; Khan, Nasarullah; Zafar, Hina (Biological Sciences - PJSIR, 2013)